2021
DOI: 10.1029/2020gl091487
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Amundsen Sea Low by Antarctic Orography

Abstract: The Amundsen Sea Low (ASL) is a distinctive feature of the Southern Hemisphere high latitude atmospheric circulation, regulating regional Antarctic climate, meridional heat transport, ocean circulation, and sea‐ice in the Amundsen‐Bellingshausen Seas. Most previous research on the ASL has focused on its variability with only a few studies attempting to understand why the climatological ASL exists. These studies have proposed different hypotheses to explain the presence of the ASL, however, a clear understandin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…By developing an ASL index, Hosking et al [43] calculated the relative ASL pressure with regard to the background pressure by subtracting the area-averaged MSLP over the Bellingshausen and Amundsen seas (60-70 • S, 170-290 • E) to isolate the regional ASL variability and found that the strength of the relative ASL pressure is greatest in JJA (not shown). This seasonal ALS climatology is generated by the interaction between the topography of West Antarctica and the westerly wind jet [44]; therefore, it is speculated that the annual zonal-wind cycle plays an important role in the seasonal modification of the ASL. If atmospheric disturbance occurs by teleconnection, the ASL becomes deeper or weaker over time.…”
Section: Basic Flow and Teleconnectivity In Different Seasonsmentioning
confidence: 99%
“…By developing an ASL index, Hosking et al [43] calculated the relative ASL pressure with regard to the background pressure by subtracting the area-averaged MSLP over the Bellingshausen and Amundsen seas (60-70 • S, 170-290 • E) to isolate the regional ASL variability and found that the strength of the relative ASL pressure is greatest in JJA (not shown). This seasonal ALS climatology is generated by the interaction between the topography of West Antarctica and the westerly wind jet [44]; therefore, it is speculated that the annual zonal-wind cycle plays an important role in the seasonal modification of the ASL. If atmospheric disturbance occurs by teleconnection, the ASL becomes deeper or weaker over time.…”
Section: Basic Flow and Teleconnectivity In Different Seasonsmentioning
confidence: 99%
“…The ASL is a permanent low pressure system located between the Bellingshausen Sea and the Ross Sea (Raphael et al., 2016), which plays an essential role in modulating the West Antarctic climate by controlling meridional wind (Turner et al., 2016) and owns the largest atmospheric variability in the Southern Hemisphere (Lachlan‐cope et al., 2001). Previous studies have revealed that ASL variations are strongly affected by the Southern Hemisphere westerlies (Goyal et al., 2021), the Southern Annular Mode (SAM; Liu et al., 2021), and other climate systems in the high latitudes (Turner et al., 2013). In the recent decades, there has been a growing interest in the relationship between the ASL and tropical climate systems like ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…The direction and strength of surface winds are playing a dominant role in the variability of Antarctic sea ice through two main processes: (a) cold or warm air advection and (b) wind-driven sea ice movement (e.g., M. M. Holland et al, 2018; P. R. Holland & Kwok, 2012;Kwok et al, 2017;Simpkins et al, 2012;Turner et al, 2015Turner et al, , 2016Raphael et al, 2016). The Amundsen Sea Low (ASL) is a persistent low-pressure system located offshore of western Antarctica with its existence due to the interaction between the westerly winds and the topography of Antarctica (Goyal et al, 2021). The ASL has been shown to play a key role in changes in surface winds and regional Antarctic sea ice extent.…”
mentioning
confidence: 99%
“…R. Holland & Kwok, 2012;Kwok et al, 2017;Simpkins et al, 2012;Turner et al, 2015Turner et al, , 2016Raphael et al, 2016). The Amundsen Sea Low (ASL) is a persistent low-pressure system located offshore of western Antarctica with its existence due to the interaction between the westerly winds and the topography of Antarctica (Goyal et al, 2021). The ASL has been shown to play a key role in changes in surface winds and regional Antarctic sea ice extent.…”
mentioning
confidence: 99%